Logistic function explains the growth dynamics of different types of shoots of four olive cultivars grown in a super high-density orchard - Costanza, Leonardo; Pinto, Diego Maria; Pinto, Luigi; Vivaldi, Gaetano Alessandro; Camposeo, Salvatore (Frontiers in Plant Science, 2025)
IntroductionThe olive tree (Olea europaea L.) has cultural, economic, and environmental importance in the Mediterranean region. In the last two decades, olive cultivation has shifted from low-density to super high-density (SHD) planting systems. These systems are characterized by narrow hedgerows of low-vigor, early-bearing cultivars, allowing full mechanization. However, limited information are available on shoot growth dynamics of the olive tree under the SHD system. This study aimed to investigate the shoot growth dynamics of four olive cultivars (‘Arbequina’, ‘Coratina’, ‘Frantoio’, and ‘Urano’) by modeling the elongation of different shoot types (apical proleptic, lateral proleptic, sylleptic) under SHD conditions.MethodsA four-year field study was conducted on four olive cultivars (‘Arbequina’, ‘Coratina’, ‘Frantoio’, and ‘Urano’) grown in an SHD orchard under Mediterranean climate. Apical proleptic, lateral proleptic, sylleptic, and adventitious shoots were monitored. Logistic regression was applied to model shoot elongation, and statistical analyses were conducted to assess the influence of cultivar, shoot type, and year. Moreover, the effect of crop load and temperature on shoot growth was also evaluated.Results and DiscussionNo significant difference was shown between the type of shoot and cultivar. Results indicate that single-phase logistic growth was the most common pattern, except for the lateral proleptic shoots of ‘Coratina’ and adventitious of ‘Urano’, where a second vegetative flush occurred. No correlation of Growing Degree Days with the shoot growth was observed. As confirmed in previous studies, crop load showed a negative influence on shoot elongation. Particularly for Arbequina’s adventitious shoots, Coratina’s and Frantio’s sylleptic shoots and Urano’s lateral proleptic, this trend was observed. This evidence showed the potential competition between the reproductive and vegetative cycle for assimilates. To our knowledge, this is the first report addressing the vegetative growth dynamics of four different shoot types of four distinct olive cultivars with different vigor in an SHD system. These findings are essential for optimizing cultivar-specific agricultural strategies (e.g. canopy management and irrigation) to achieve an optimal yield and sustainable cultivation. Future research will explore the vegetative growth dynamics, including other factors such as trunk diameter, Leaf Area Index, and water stress indices.